PENGUATAN PROMOSI DESA WISATA BERBASIS KEARIFAN DI DESA PUJON KABUPATEN MALANG - Nuurlaily, Siti; Anak Agung Sagung Alit Widyastuty; Annisa Budhiyani Tribhuwaneswari (LPPM Universitas PGRI Adi Buana Surabaya, 2020)
Abstract Tourism village is largely based in local wisdom is a form of integrated activities between attractions, accommodation, supporting facilities and additional facilities in the form of village management presented in the structure of community life that is bound by traditional procedures and norms that apply in the village. The development of sustainable tourism villages reguires the participation of local communities in all phases of development starting from the planning, implementation and supervision and control stages. Pujon Kidul Village in Pujon subdistrict, Malang regency is one of the tourist villages developed by the village community, which has tourism potential from the agriculture, livestock and small to mediun industries which is supported by the geographical and climatological conditions of the region. The purpose of this activity is to strengthen the promotion of village teourism based in local wisdom by identifying the potential of the Pujon Kidul village tourism area. Approach to the implementation of community service using the Rural Appraisal Approach (RAA) through a Group Discussion Forum (FGD) between the Pujon Kidul village apparatus, the Tourism Awarness Group (Pokdarwis) and the representatives of the village community. The results of this activity are strengthening promotion through a catalog of tourism village potentials and understanding of village afficials, the community and the private sector in planning the development of tourism villages through the utilization of the potential of geography, agriculture, animal husbandry and plantations in the tourism village of Pujon Kidul District of Pujon Malang Regency which begore socialization and counselling was 32% to 96%.. Keyword : Local Wisdom, Tourism Potentials, Tourism Village Abstrak Desa wisata sebagaian besar berbasis pada kearifan lokal desa adalah bentuk kegiatan terintegrasi antara atraksi, akomodasi, fasilitas pendukung dan fasilitas tambahan berupa manajemen desa yang disajikan dalam struktur kehidupan masyarakat yang terikat dengan prosedur tradisi dan norma yang berlaku di desa. Pengembangan desa wisata yang berkelanjutan membutuhkan partisipasi masyarakat lokal dalam seluruh fase pengembangan mulai dari tahap perencanaan, implementasi dan pengawasan serta pengendalian. Desa Pujon Kidul di Kecamatan Pujon Kabupaten Malang merupakan salah satu desa wisata yang dikembangkan oleh masyarakat desa, memiliki potensi wisata dari sector pertanian, peternakan dan industry kecil ke menengah yang didukung kondisi geografi dan klimatologi wilayahnya. Tujuan dari kegiatan ini adalah penguatan promosi desa wisata yang berbasis kearifan lokal dengan mengidentifikasi potensi kawasan wisata desa Pujon Kidul. Pendekatan – pendekatan pelaksanaan pengabdian dengan menggunakan metode Rural Appraisal Approach (RAA) melalui Forum Group Diskusi (FGD) antara aparatur desa Pujon Kidul, Kelompok Sadar Wisata (pokdarwis) dan perwakilan masyakat desa. Hasil dari kegiatan ini adalah penguatan promosi melalui katalog potensi desa wisata dan pemahaman aparatur desa, masyarakat dan pihak swasta dalam perencanaan pengembangan desa wisata melalui pemanfaatan potensi geografi, pertanian, peternakan dan perkebunan di desa wisata Pujon Kidul Kecamatan Pujon Kabupaten Malang yang sebelum sosialisasi dan penyuluhan sebesar 32% menjadi 96%. Kata kunci : Desa Wisata, Potensi wisata, Kearifan Lokal.